2022
DOI: 10.3390/jcm11071793
|View full text |Cite
|
Sign up to set email alerts
|

Malignant Transformation Rate of Oral Submucous Fibrosis: A Systematic Review and Meta-Analysis

Abstract: Oral submucous fibrosis (OSF) is a chronic progressive condition affecting the oral cavity, oropharynx and upper third of the oesophagus. It is a potentially malignant disorder. The authors collated and analysed the existing literature to establish the overall malignant transformation rate (MTR). A retrospective analysis of medical and dental scientific literature using online indexed databases was conducted for the period 1956 to 2021. The quality of the enrolled studies was assessed by the Newcastle-Ottawa S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 27 publications
1
32
0
Order By: Relevance
“…Moreover, the long-term use of areca nut can induce the production of free radicals and reactive oxygen species, leading to a high rate of oxidation/peroxidation of unsaturated fatty acids, which affects the essential components of cell membranes [6]. The study showed that the composition of betel nut products, the frequency and duration of betel nut consumption may all affect the malignant transformation rate of the disease [7] Currently, the treatment of OSF mainly includes physical therapy, hyperbaric oxygen therapy, drug therapy, and surgical treatment [8]. Drug therapy is the most common treatment, and available drug treatments include steroids, exogenous enzymes, multivitamins and micronutrients, peripheral vasodilators, human placental extracts, and other therapeutic agents.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the long-term use of areca nut can induce the production of free radicals and reactive oxygen species, leading to a high rate of oxidation/peroxidation of unsaturated fatty acids, which affects the essential components of cell membranes [6]. The study showed that the composition of betel nut products, the frequency and duration of betel nut consumption may all affect the malignant transformation rate of the disease [7] Currently, the treatment of OSF mainly includes physical therapy, hyperbaric oxygen therapy, drug therapy, and surgical treatment [8]. Drug therapy is the most common treatment, and available drug treatments include steroids, exogenous enzymes, multivitamins and micronutrients, peripheral vasodilators, human placental extracts, and other therapeutic agents.…”
Section: Introductionmentioning
confidence: 99%
“…Oral submucous fibrosis (OSMF) is defined as a chronic scarring disease that severely affects the oral cavity, oropharynx, and sometimes the oesophagus [ 1 , 2 ]. It represents a precancerous disorder and the transformation into oral squamous cell carcinoma has been found in 6%–30% cases of OSMF [ 1 , 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Oral submucous fibrosis (OSMF) is defined as a chronic scarring disease that severely affects the oral cavity, oropharynx, and sometimes the oesophagus [ 1 , 2 ]. It represents a precancerous disorder and the transformation into oral squamous cell carcinoma has been found in 6%–30% cases of OSMF [ 1 , 3 ]. OSMF is characterized by abnormal accumulation of collagen concomitant with progressive fibrosis in the submucosal connective tissues and limit mouth opening and tongue movement, leading to impingement on speech and swallowing [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…The published medical data on oral submucous fibrosis establishes the fact that arecanut plays an important role in the pathogenesis of oral submucous fibrosis 5 . Patients with Oral Submucous Fibrosis have been reported to develop malignancy that is oral squamous cell carcinoma at a higher rate compared to other oral potentially malignant disorders 6 .…”
Section: Introductionmentioning
confidence: 99%
“…The pre malignant characteristic of OSF was first described by paymaster in 1956 8 . Pindborg et al have reported malignant transformation rate to be 2.8 % while Murthy et al 1985 has reported it to be as 7.6 % over a period of 15 years but in 2022 a meta-analysis by Murthy V et al reported the malignant transformation rate to be 4 % 9,10,11 .…”
Section: Introductionmentioning
confidence: 99%